Olig2-Lineage Astrocytes: A Distinct Subtype of Astrocytes That Differs from GFAP Astrocytes - Tatsumi, Kouko; Isonishi, Ayami; Yamasaki, Miwako; Kawabe, Yoshie; Morita-Takemura, Shoko; Nakahara, Kazuki; Terada, Yuki; Shinjo, Takeaki; Okuda, Hiroaki; Tanaka, Tatsuhide; Wanaka, Akio (Frontiers in Neuroanatomy, 2018)
Astrocytes are the most abundant glia cell type in the central nervous system (CNS), and are known to constitute heterogeneous populations that differ in their morphology, gene expression and function. Although glial fibrillary acidic protein (GFAP) is the cardinal cytological marker of CNS astrocytes, GFAP-negative astrocytes can easily be found in the adult CNS. Astrocytes are also allocated to spatially distinct regional domains during development. This regional heterogeneity suggests that they help to coordinate post-natal neural circuit formation and thereby to regulate eventual neuronal activity. Here, during lineage-tracing studies of cells expressing Olig2 using Olig2CreER; Rosa-CAG-LSL-eNpHR3.0-EYFP transgenic mice, we found Olig2-lineage mature astrocytes in the adult forebrain. Long-term administration of tamoxifen resulted in sufficient recombinant induction, and Olig2-lineage cells were found to be preferentially clustered in some adult brain nuclei. We then made distribution map of Olig2-lineage astrocytes in the adult mouse brain, and further compared the map with the distribution of GFAP-positive astrocytes visualized in GFAPCre; Rosa-CAG-LSL-eNpHR3.0-EYFP mice. Brain regions rich in Olig2-lineage astrocytes (e.g., basal forebrain, thalamic nuclei, and deep cerebellar nuclei) tended to lack GFAP-positive astrocytes, and vice versa. Even within a single brain nucleus, Olig2-lineage astrocytes and GFAP astrocytes frequently occupied mutually exclusive territories. These findings strongly suggest that there is a subpopulation of astrocytes (Olig2-lineage astrocytes) in the adult brain, and that it differs from GFAP-positive astrocytes in its distribution pattern and perhaps also in its function. Interestingly, the brain nuclei rich in Olig2-lineage astrocytes strongly expressed GABA-transporter 3 in astrocytes and vesicular GABA transporter in neurons, suggesting that Olig2-lineage astrocytes are involved in inhibitory neuronal transmission.